MATHEMATICAL MODEL AND ALGORITHM FOR CALCULATION OF MANAGEMENT PROCESSES FOR ADVANCED TRAINING OF SPECIALISTS IN THE HYDROPOWER INDUSTRY - Isroilova Lola Sunnatovna (American Journals Publishing, 2024)
The article deals with the practical issue of managing the educational process on the example of the hydropower industry. A mathematical model of the problem was created using the principle of systematic approach of management theory and the elements of set theory. A calculation algorithm for solving the problem is created, the results of the calculation experiment are presented, and practical recommendations are given.
Keywords: management theory, system, systematic approach, production, networks, educational process, training, object, subject, teacher, mathematical model, set, subset, intersection, union, information matrix, algorithm, computational experiment